Approximation of Functions by the Szász-Mirakjan-Kantorovich Operator. (19th May 2019) - Draganov, Borislav R.; Gadjev, Ivan
Abstract: We characterize the approximation of functions in the Lp -norm by the Szász-Mirakjan-Kantorovich operator. We prove a direct and a strong converse inequality of type B in terms of an appropriate K -functional.